La incidencia del suicidio como problema público en la construcción de la Política Distrital de Salud Mental Bogotá 2015 - 2025 (2024)
In May 2013 at the 66th World Health Assembly, the first action plan on mental health was adopted giving a special focus on suicide prevention, thus proposing a 10% reduction worldwide by 2020, through plans and projects recommended to be implemented by each member state. From this milestone, from the national and district governments of the time, public policies on mental health were developed, demonstrating that the agenda of this public problem is directed and guided by the international agenda, the plans and projects established go hand in hand with everything proposed by the WHO.